Anthropogenic climate change and heat effects on health. (10th May 2019) - Christidis, Nikolaos; Mitchell, Dann; Stott, Peter A.
Abstract: Increasing extreme temperatures linked to human influence amplify thermal stress and can lead to decreases in work productivity and increases in heat‐related mortality. However, studies assessing in a formal statistical way the contribution of climate change to such impacts remain sparse. Two new indices are introduced here that measure the effect of anthropogenic climate change on the intensity and frequency of health‐relevant heat extremes. Maximum daily temperature data from observations and climate models are used to compute annual index values in different regions around the world. The models employed in the study are evaluated against observational data and only the 10 best are retained for the analysis. Human‐induced warming that leads to an increase in heat‐related deaths has reached about a degree in all continents and is projected to exceed 3° by 2100. All regions currently experience at least 10 additional days per year when thermal deaths are expected to occur, but the number is several times higher in warmer tropical regions, where it is estimated to exceed 100 days by the end of the century. Significant positive trends may also arise in smaller‐scale areas, as shown for central England. Adaptation to the warmer present‐day climate would take the edge off the intensity of warming conducive to a rise in heat mortality by 2100, reducing it by about a degree, but would have a more moderate effect on the frequency of heat mortality days. Index values are also computed with data from the Hadley Centre's attribution system, and annual assessments of the associated impacts are made, which are envisaged to become part of a developing climate service. A first application to the United Kingdom for two recent years demonstrates the kind of attribution information that can be made available to users. Abstract : Human activity has increased warming that gives rise to heat‐related deaths by about a degree in all continents, projected to increase to 3° by 2100. There are at least 10 days of dangerous warming in a year, but more in tropical regions. If societies were to adapt to the present‐day climate, warming associated with increases in mortality would reduce by about a degree in 2100, but the effect on the frequency of heat mortality days would be more moderate. In the figure, maps of high risk warming (HRW) and high risk days (HRD) index trends for the periods 1900–2020 (a, c) and 1900–2100 (b, d). The plotted trends show the mean estimate of 10 CMIP5 models. The model simulations were extended to the end of the century with the RCP4.5 scenario.